Increased apoptosis of host cells and tumor cells in the invasion front of colorectal liver metastases - Bandapalli, Obul Reddy; Hariri, Nawid; Macher-Göppinger, Stephan; Kahlert, Christoph; Schirmacher, Peter; Brand, Karsten (Anticancer research, 2011)
Background: The invasion front of colorectal liver metastases is an area of intensive tumor cell-host cell contact. Materials and Methods: In a xenograft nude mouse model, we analyzed whether apoptosis induction is a prominent feature in this active area, perhaps offering new modalities of therapeutic intervention. Results: Using global gene expression technology, an over-representation of apoptosis-related biological themes in the invasion front was observed. A combination of apoptosis-specific TUNEL/DAPI staining and cell type-specific staining showed that all examined cell types, including tumor cells, hepatocytes, endothelial cells, macrophages and hepatic stellate cells, displayed increased apoptosis in the invasion front. Evaluation of gene expression of the death receptor/ligand pairs TRAILR2 /TRAIL and FAS/FASL indicated that tumor cells overexpressed TRAILR2 and FAS, whereas host cells expressed TRAIL and FASL. Conclusion: This data indicates that the invasion front of colorectal liver metastases is an area of prominent pro-apoptotic activity, involving known death receptor/ligand interactions.